Understanding and Application of Culturally Diverse Issues Within University Settings - Hall, Barry L.; Kulig, Judith C.; Thorpe, Karran; Pfeutl, Lucia (Canadian Journal of Higher Education, 1998)
This qualitative study focused on exploring the knowledge and beliefs of university faculty, staff and students regarding: the effects of multi-culturalism and immigration on their professional lives; the influence of cultural issues within the university setting; and, finally, the teaching and learning needs of culturally diverse students. The major findings include the limited knowledge base held by all groups in the sample about multi- culturalism and immigration with subsequent little effect on their professionall lives. However, of the three groups, the student group more readily recognized that they have little preparation for the multicultural interactions that will occur in their future professional practices. Although some faculty members included other teaching experiences and strategies to expose students to diversity, they also admitted to a lack of expertise in this area.